Characterization of tissue‐specific differences in cell wall pectic polysaccharides of carrot root. Issue 4 (9th February 2021) - Peng, Jian; Bi, Jinfeng; Yi, Jianyong; Lyu, Jian; Zhao, Yuanyuan; Xu, Yujuan; Yu, Yuanshan
Abstract: This study investigated the physicochemical characteristics of CWPs from epidermis, cortex, and stele of carrot. The CWPs extracted from cortex contained the highest content of galacturonic acid (GalA), as well as the highest degree of methylation. Compared to Na2 CO3 extractable fraction (NEF) and water extractable fraction (WEF), chelator extractable fraction (CEF) contained higher GalA content, and it was identified with more linear homogalacturonan (HG). The highest amounts of Gal, Ara, and Rha were obtained in NEF extracted from cortex, suggesting that abundant side chains attached to pectic backbone of NEF and formed "hairy region." In addition, gentle changes of the molar mass along with tissue zones were observed in different pectic fractions. However, the molar mass of NEF was always higher than WEF regardless of the tissues. According to FTIR, the configurations of all CWPs were similar and exhibited typical structural properties of pectic polymers. Practical applications: Cell wall pectic polysaccharides (CWPs) are important macromolecules which highly correlated with food products qualities. The CWPs extracted from epidermis, cortex, and stele of carrot root were prepared and their physicochemical characteristics were evaluated. Detailed characteristics of tissue‐specific differences in CWPs of carrot root could provide more fundamental information for carrot‐related food processing.